Twitter and the Struggle to Transform the Object: A Study of Clean Coal in the 2017 Australian Energy Policy Public Debate - Kristin Demetrious (Journal of Public Interest Communications, 2019)
This paper investigates unusually high spikes in Twitter engagement in Australia in February 2017 invoking the 2014 Peabody Energy global public relations campaign Advanced Energy for Life (AEFL) trope clean coal. Focusing on peak Twitter events, it asks: What caused the spike, what was amplified and signified by the dominant tweeters, and what was the content and tenor of discussion generated? Applying discourse analysis to an archive of Australian-based Twitter activity, the research argues that despite widespread ridicule of clean coal as oxymoronic by contemporary publics, the increased engagement provided unintended impetus for the PR campaign objectives. The research contributes to greater understanding of the reach, influence, and limitations of Twitter-based public debate.